High grade neuroendocrine carcinoma of the urinary bladder treated by radical cystectomy. Issue 6 (October 2015) - Gupta, Sounak; Thompson, R. Houston; Boorjian, Stephen A.; Thapa, Prabin; Hernandez, Loren P. Herrera; Jimenez, Rafael E.; Costello, Brian A.; Frank, Igor; Cheville, John C.
<x xml:space="preserve">Abstract</x> Summary High grade neuroendocrine carcinomas (HGNEC) treated by cystectomy often carry an original diagnosis of typical urothelial carcinoma (UC). The correct diagnosis of HGNEC is critical in influencing the decision for early chemotherapy, potentially followed by cystectomy. The objective of this study was to characterise the features of HGNEC treated by radical cystectomy. The study consisted of 79 patients with HGNEC including small cell (68 patients), large cell neuroendocrine (LCNEC) (5 patients) and mixed neuroendocrine (mixed-NEC) carcinoma (6 patients) matched with 122 patients with UC, treated at our institution between 1987 and 2014. Morphometric analysis for cell and nuclear size as well as immunophenotyping for neuroendocrine markers and cell-cycle regulators were applied to tissue microarrays. Small cell, LCNEC and mixed-NEC are a morphological spectrum of high grade neuroendocrine carcinoma with overlapping histological features, identical immunophenotype, Ki-67 proliferative rate and patient outcomes. Finally, the nuclear size criteria is misleading as HGNEC, particularly cases of LCNEC and mixed-NEC, may have enlarged nuclei compared to small cell carcinomas and are more prone to be misdiagnosed as UC, thereby preventing appropriate management.